Antiphospholipid Antibody Syndrome: Pathogenesis, Diagnosis, and Management in Pregnancy. Issue 1 (July 2019) - Khangura, Raminder Kaur; Cooper, Shontreal; Luo, Guo-Yang
Abstract : Abstract: Antiphospholipid antibody syndrome is an autoimmune disorder that primarily affects reproductive age women and poses significant obstetric complications. Here we review the pathogenesis, diagnosis, obstetric complications, and management in women with antiphospholipid antibody syndrome.